The future of universities - Abdulkarem Al Shawtari, Ahmed; Mariwa, Amal Jumah; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
Changing times warrant a change in the way companies and organizations deal with their stakeholders and shareholders. In other words, predictable and unpredictable environmental factors push organizations to keep changing and improving their strategies in order to have competitive advantage over other organizations in the market. In the case of universities, not only does it have competitors within the educational sector but it also has within other sectors. This makes it challenging for a university to remain relevant in the next few years. This paper examined the different environmental factors that are affecting the universities. It has established that in order to have competitive advantage over its competitors, it has to re-evaluate its business model and processes. After studying and analyzing BMC and value proposition canvas, the study has discovered that to be a “the future of universities”, a university needs streamline its business model according to the needs of the customer segments by offering specializations on sought after degrees (e.g. Islamic banking), training (online), develop an MOOC, as well as provide other online educational resources for the customers. This study forms a basis for future research and work on the ever changing environmental factors that continuously affect a university.